(3bhGWY GdCOdI aj CUhd Gdabgs - (3GdSeYGfj , efUhQ Hf eMeO Hf YHO GdLHGQ Hf CMeO GdJejej,J (B489 (3g` s ((3Ydi Hf YHO GdcGai GdSHci s)
(3ChdgG (B:s
(3jHJOF HHGH GdbjGS hGdELJgGO s
(3BNQgG (B:s
(3jfJgi HPcQ aUdkG ai EfaSGN GdYbhO GdTQYjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HghGeTgG JYdjbGJ HNW GdSHcis
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3CUhd Gdabgs